Refleksi Kehidupan Gereja Perdana dalam Praktik Gereja Virtual - Jimmy Lizardo (EPIGRAPHE (Jurnal Teologi dan Pelayanan Kristiani), 2022)
. The virtual church is a future church design that allows all human spiritual activities, such as worship, cell communities, prayer services, counseling, sacraments, evangelism, and so on, to enter soon a new era where the role of human beings is becoming increasingly insignificant and replaced with a touch of internet-based technology. The development of technology, with all its sophistication, has shifted the definition of the church. There is a characteristic of the true church, which is that 'koinonia' (communion) cannot be implemented virtually. This study aims to conduct a biblical study of the true meaning of digital ecclesiology to find whether the virtual church violates the rules of God's word or not. As well as looking for biblical patterns of spiritual life in building a virtual church. Using qualitative methods with a literature study approach through the source of books and literature as a research reference. The conclusion of this study is that the practice of virtual churches does not violate the rules of God's word; however, virtual churches need to build strong relationships between members (koinonia/communion), as the early congregations did in Acts 2:42-47, becoming a pattern (patron) of building virtual churches in today's era.AbstrakGereja virtual adalah rancangan gereja masa depan yang memungkinkan semua aktivitas rohani manusia seperti ibadah, komunitas sel, pelayanan doa, konseling, sakramen, penginjilan dan sebagainya akan segera memasuki era baru, di mana peran manusia menjadi semakin tidak signifikan dan tergantikan dengan sentuhan teknologi berbasis internet. Perkembangan teknologi dengan segala kecanggihannya membuat definisi gereja mengalami pergeseran. Ada karakteristik gereja sejati, yaitu koinonia (persekutuan) yang tidak mampu diterapkan secara virtual. Penelitian ini bertujuan melakukan kajian biblis makna eklesiologi digital yang sesungguhnya, untuk menemukan apakah gereja virtual menyalahi kaidah firman Tuhan atau tidak? Serta mencari pola kehidupan rohani yang Alkitabiah dalam membangun gereja virtual. Menggunakan metodekualitatif dengan pendekatan studi pustaka, melalui sumber buku-buku dan literatur sebagai acuanpenelitian. Kesimpulan penelitian ini adalah praktik gereja virtual tidak menya-lahi kaidah firman Tuhan, namun demikian, gereja virtual perlu membangun relasi yang kuat antar-anggota (koinonia/persekutuan), seperti yang dilakukan jemaatmula-mula dalamKisah Para Rasul2:42-47, menjadi sebuah pola (patron) membangun gereja virtual di era sekarang ini.